Determinants of hepatitis B virus infection among pregnant women in Bench Sheko zone, Southwest Ethiopia: a case-control study - Yosef, Tewodros; Eyasu, Ephrem; Shifera, Nigusie; Abebe, Gossa Fetene; Girma, Desalegn; Habte, Aklilu; Ahmed, Ahmed Fentaw; Asefa, Adane (Frontiers in Global Women's Health, 2024)
BackgroundHepatitis B Virus (HBV) infection during pregnancy poses serious risks by raising the likelihood of chronic infection in newborns by 90% and the risk of cirrhosis and liver cancer by 25% in chronic infections. This study aimed to identify determinants of HBV infection among pregnant women in the Bench Sheko zone, Southwest Ethiopia.MethodsAn unmatched case-control study was conducted from May 15 to July 15, 2022, in selected health facilities of the Bench Sheko zone, Southwest Ethiopia. Medical charts were reviewed to collect the HBsAg status of participants, as all pregnant women attending antenatal care underwent routine screening. It involved 228 pregnant women (76 HBV-positive cases and 152 HBV-negative controls). Data were collected using structured questionnaires, and analyzed using SPSS 21. A multivariable logistic regression was performed to identify significant determinants of HBV infection, and statistical significance was declared at p-value <0.05.ResultsAfter controlling potential confounders, having no formal education (AOR = 4.94, 95% CI: 2.01, 8.29; P = 0.007), urban residency (AOR = 2.56, 95% CI: 1.43, 6.86; P = 0.010), history of unsafe abortion (AOR = 3.87, 95% CI: 2.17, 6.98; P < 0.001), sharing sharp materials (AOR = 8.43, 95% CI: 5.54, 10.9; P < 0.001), contact with HBV-infected persons in the family (AOR = 2.18, 95% CI: 1.72, 4.87; P < 0.001), tribal scarification (AOR = 3.23, 95% CI: 1.24, 8.91; P = 0.017), and history of unsafe tooth extraction (AOR = 4.52, 95% CI: 2.18, 9.76; P = 0.039) were identified as significant predictors of HBV infection.ConclusionThe study identifies multiple factors contributing to HBV infection in pregnant women. Therefore, it is crucial to promote safe abortion practices and the responsible use of sharp materials, avoid high-risk contact with infected individuals within the family, raise awareness about the risks associated with tribal scarification while advocating for safer practices, and offer education on safe tooth extraction methods to reduce the risk of HBV.